Efektivitas Implementasi Penyimpanan Logistik Obat Dengan Metode Fifo Dan Fefo Dalam Menjaga Ketersediaan Obat di Gudang Farmasi - Nani Yuniar; Zarah Amalia; Wa Ode Fimpian Andi; Zahra Nuril Anwar; Tesya Safitri; Suci Indar Faradhiba; Andi Firman Ardiansyah; Ratu Banneringgi; Sabrina Salsabilah; Rosmawati; Sendi Selfiana Kaliele; Revi Ardianti; Qanita Luthfiyah Odesara (Jurnal Sains Farmasi Dan Kesehatan, 2025)
The purpose of this study is to ascertain how well pharmaceutical warehouse pharmaceuticals are kept available through the employment of the FIFO (First In First Out) and FEFO (First Expired First Out) approaches in the drug logistics storage system. Descriptive qualitative research methodology is employed, and data is gathered by document analysis, in-depth interviews, and observation. The success of applying the FIFO and FEFO methods to the degree of drug availability, the drug receiving process, the storage and distribution flow, and the drug stock sorting were the four primary areas of attention for this study. It is anticipated that the study's findings will assist pharmaceutical warehouse management in enhancing the efficacy and efficiency of the pharmaceutical logistics system and serve as a guide for future medication management policy development.